2019
DOI: 10.1038/s41422-019-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

BubR1 phosphorylates CENP-E as a switch enabling the transition from lateral association to end-on capture of spindle microtubules

Abstract: Error-free mitosis depends on accurate chromosome attachment to spindle microtubules, powered congression of those chromosomes, their segregation in anaphase, and assembly of a spindle midzone at mitotic exit. The centromere-associated kinesin motor CENP-E, whose binding partner is BubR1, has been implicated in congression of misaligned chromosomes and the transition from lateral kinetochore-microtubule association to end-on capture. Although previously proposed to be a pseudokinase, here we report the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 63 publications
4
62
0
Order By: Relevance
“…Notably, this regulation of BUB1 activity by the BUBR1 pseudokinase may also explain the kinase activity reported in BUBR1 immunoprecipitates, and why this activity is sensitive to mutation of BUBR1 catalytic triad residues, or loss of the BUBR1 kinase which we have shown here tempers BUB1 autophosphorylation 4143, 73 . In agreement with this, BUB1 and BUBR1 form relatively stable complexes in vitro 44 , and previous work has shown that BUBR1-associated kinase activity is particularly sensitive to BUB1 inhibitors 38 .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Notably, this regulation of BUB1 activity by the BUBR1 pseudokinase may also explain the kinase activity reported in BUBR1 immunoprecipitates, and why this activity is sensitive to mutation of BUBR1 catalytic triad residues, or loss of the BUBR1 kinase which we have shown here tempers BUB1 autophosphorylation 4143, 73 . In agreement with this, BUB1 and BUBR1 form relatively stable complexes in vitro 44 , and previous work has shown that BUBR1-associated kinase activity is particularly sensitive to BUB1 inhibitors 38 .…”
Section: Discussionsupporting
confidence: 62%
“…The finding that CENP-E played no discernable role in B56 recruitment and SAC silencing was surprising, considering the effect of its inhibition on BUBR1 hyperphosphorylation documented by us and others 4143, 73 . However, when we examined KARD phosphorylation in CENP-E depleted cells further, we found that while S676 phosphorylation was reduced, as we have shown before, S670 phosphorylation was increased ( 52 and Sup Fig 5A-B ).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, this motif has been found to be dispensable for catalytic activity in an atypical catalytically active coccidian kinase, which has been termed WNG1 (with no glycine-1) (43). A recent study suggests a catalytically active, druggable conformation in Drosophila BubR1 that can directly phosphorylate the motor protein centromereassociated protein E (CENP-E) (44). This likely differentiates it from human BubR1, which is reported to be an inactive pseudokinase (45) lacking a Gly-rich loop and that does not bind detectably to ATP (46).…”
Section: Structural Biology As a Key Driver In The Pseudokinase And Pmentioning
confidence: 99%
“…10 Settling these discrepancies is particularly important now that BubR1 has been implicated in key biological processes such as maintenance of genomic integrity, cancer, senescence, and aging. In a recent paper published in Cell Research, Huang et al 11 provide compelling evidence that BubR1 is indeed an active kinase. Their first piece of evidence came from resolving the crystal structure of the BubR1 kinase domain.…”
mentioning
confidence: 99%